New approach to researching the development level of the creatosphere in human-centered economy in Russia - S. I. Nasyrova (Russian Journal of Economics and Law)
Objective: to develop conceptual provisions of human-centered economy by forming a new approach to the study of the creatosphere as a constituent element of the said economic system in order to develop its management.   Methods: analysis, synthesis, content analysis, scheme of contradiction, linear scaling method, minimax normalization.   Results: the characteristic of the creatosphere of the human-centered economy is revealed from the viewpoint of satisfying the individual’s needs in creativity; the creatosphere structure is analyzed as an element covering all spheres of the economic system under consideration; the model of homeostasis of the human-centered economy is developed through identifying its elements-opposites (on the one hand – natural and material spheres, services, social sphere, infosphere, digital and cognitive spheres, on the other hand – creatosphere), as well as the model of the basic resource (flow of ideas) and regulator (human needs); the predetermining role of the creatosphere in the development of the said economic system is outlined; the contradictions are revealed at the level of human-centered economy, the resolution of which contributes to the development of an individual and the economic system as a whole.   Scientific novelty: it consists in the development of a methodology for assessing the creatosphere and testing it on the Russian subjects. Unlike those available in the literature, the methodology allows comprehensively assessing the creatosphere development as an element that affects the human-centered economy as a whole. The novelty consists also in defining a vector in the creatosphere management based on the formed approach to its research through the upscaling of best regional practices.   Practical significance: the results of comprehension of the human-centered economy creatosphere through the scheme of contradictions may serve as a basis for further research in order to build a scientifically sound theory of the said economic system and to form directions for resolving the identified contradictions. The study results are the basis to further define the development level of the Russian human-centered economy in order to develop measures for its effective management.